LEONTOPODIUM ALPINUM CASS. ’HELVETIA’, A NEW HYBRID EDELWEISS - Vouillamoz, J.; Carron, Claude-Alain; Baroffio, C. A.; Carlen, C. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Edelweiss (Leontopodium alpinum Cass. Asteraceae) is the most emblematic plant of the Alps. Wild collections is strictly forbidden or limited. Since natural populations show a high degree of morphological variability, a breeding program was carried out to obtain a high quality, productive and homogenous variety for cultivation. Breeding was facilitated by a particular reproduction system. Edelweiss “flowers” are in reality a capitulum of capitula: a star-shape involucrum of bracts surrounds 5-10 capitula (inflorescences containing numerous tiny flowers) clustered in one capitulum. As a rule, an Edelweiss plant contains both hermaphrodite and female flowers (gynomonoecy). However, a few rare occurrences of hermaphrodite only and female only individuals (gynodioecy) have been observed. We used this biological feature to create hybrid clones from five female only plants (mother-plants) pollinated by four hermaphrodite plants (father-plants). We obtained 19 hybrids and compared them to three selected hermaphrodite and two wild populations from the Swiss Alps. Hybrid plants turned out to be much more homogenous, with a higher average dry weight as well as a higher level of leontopodic acid, a recently discovered antioxidant with DNA protecting properties. The most interesting Edelweiss hybrid was named ’Helvetia’ after the Latin name of Switzerland. ’Helvetia’ is now successfully cultivated in mountainous regions of Switzerland and demand for Edelweiss ’Helvetia’ extracts by food (beverage, liquor, chocolate, etc.) and cosmetic (sunscreen, anti-aging lotions, etc.) companies has greatly increased in recent years. Acknowledgements: DSM/Pentapharm/Alpaflor, Valplantes, Weleda and Ricola for their logistic and financial support; Charly Rey for his helpful collaboration.